Advances in functional dyspepsia; traditional and beyond traditional - Nasrat, Abdullah M.; Mohamed Al Shammari, Ali Zain Abden; Alhamad, Faisal Farid; Alnefaie, Zayed Mohammed; Khalid M., Attar Razan; Alsaedi, Yousef Muflih; Alshammari, Nafesa Mohammed; Aljohani, Ibrahim Sulaiman (International Journal Of Community Medicine And Public Health, 2024)
Background: Functional dyspepsia is a clinical syndrome defined by chronic or recurrent pain, heart burn or discomfort in the upper abdomen of a variable origin. A general agreement exists on the irrelevant role played by H. pylori in the pathophysiology of most cases of functional dyspepsia. Diagnosis is based on the clinical picture and detection of H. pylori. Specific sensitive diagnostic tests are available but H. pylori serum antibodies, though non-specific, is suggested because of being cost effective as the matter of H. pylori dyspepsia is a typical subject of cost-effectiveness. The efficacy of antibiotic treatment for non-ulcer dyspepsia is controversial, different trails have given conflicting results. Antibiotic eradication treatment for non-ulcer dyspepsia symptoms had no significant effect on quality of life compared with placebo and was found costlier if compared to antacid treatment. Methods: A group of 32 males and females, children and adults with clinical symptoms of epigastric discomfort, hyperacidity and indigestion with or without distension were randomly included in study between October, 2023 and October, 2024. Their age ranged between 13-54 years; they were investigated for existence of H. pylori. Colon care and colon clear for natural eradications of H. pylori employed for them. They give natural probiotic supplements (acid butter milk) for 10 days in order to improve dyspeptic symptoms and they were followed up for 6-8 months. Results: Marked clinical improvement and disappearance of most epigastric discomfort and dyspeptic symptoms. Conclusions: H. pylori seems to be lately a major reason behind many cases of functional dyspepsia.